Extension of Bounded Linear Operators - Bajryacharya, Prakash Muni; Phulara, Keshab Raj (Journal of Advanced College of Engineering and Management, 2016)
In this article the problem entitled when does every member of a class of operators T : E → Y admit an extension operator T : X → Y in different approaches like injective spaces, separable injective spaces, the class of compact operators and extension  Into C(K ) spaces has-been studied.Journal of Advanced College of Engineering and Management, Vol. 2, 2016, page: 11-13